A suspensão dos direitos políticos na condenação criminal e os seus respectivos efeitos sociais - Carvalho de Assis, Douglas; Gross Júnior, Rauli; Arcoverde Gobbo, Lorella (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2023)
The present study aims to visualize the effects produced by article 15, III, of the Federal Constitution of 1988, which provides for the suspension of political rights in cases of criminal conviction. Briefly, by means of theoretical doctrinal research, it qualifies political rights, deducing their historical development until the current perspective of the Brazilian jurisdiction. By means of the scientific methodology of logical-deductive approach, through indirect documental research, such as legislative, doctrinaire and jurisprudential, the study compares the national treatment given to such rights with the understanding of the legislation and judgments of international courts. In the main segment, it seeks to testify the confrontation of such constitutional provision with the other constitutional principles that guide criminal law, which are proportionality and individualization, which have great relevance in penal execution. Likewise, it contrasts the suspension of political rights with the loss of citizenship, with democracy, and with the social death of the group that imports the deprivation of these fundamental rights. At the end, taking a more practical point of view, it seeks to analyze, in fact, the effects that such suspension has on the re-education of the convicted, analyzing news and reports that demonstrate that by virtue of the suppression of such rights, added to social vulnerability, obstacles to social reintegration are established. Therefore, it is verified that the constitutional provision that deprives convicted criminals of their political rights brings countless setbacks that deteriorate the objectives of penal execution, hurting democracy and fundamental rights.